Penerapan E-CRM Berbasis Web Menggunakan Metode RAD pada Showroom Wali Sanga Motor - Jihan Salsabila Arifin; Bayu Priyatna; Fitria Nurapriani; April Lia Hananto (Sekawan Institut, 2026)
Customer service at Wali Sanga Motor Showroom is still conducted manually, causing delays in information delivery, unstructured customer data management, and less optimal handling of or-ders and customer complaints. This study aims to develop a web-based Electronic Customer Rela-tionship Management (E-CRM) system using the Rapid Application Development (RAD) method to improve service effectiveness and customer relationship management. The RAD method was applied through stages of requirements planning, prototyping design, system construction, and implementation. The system was developed using the Laravel framework and MySQL database with main features including product information management, online motorcycle ordering, cus-tomer complaint services, and administrative data management. System testing was carried out using User Acceptance Test (UAT) and White Box Testing on all functional requirements that had been designed. The test results show that the system runs 100% in accordance with the UAT sce-narios and all main modules function according to user needs without any significant logical er-rors. The implementation of this E-CRM system is expected to improve service efficiency, acceler-ate responses to customers, and support integrated and sustainable management of customer ser-vice data at Wali Sanga Motor Showroom.